Carcass Trait Trends for Steers and Heifers Finished Through the Tri-County Steer Carcass Futurity Cooperative from 2002 Through 2018 - E. D. McCabe; M. E. King; K. E. Fike; M. Groves; K. G. Odde (Kansas Agricultural Experiment Station Research Reports, 2021)
Objective:The objective was to evaluate trends in carcass characteristics for steers and heifers finished through the Tri-County Steer Carcass Futurity Cooperative. Study Description:Data analyzed included 74,207 steers and 33,529 heifers finished at the Tri-County Steer Carcass Futurity Cooperative (Lewis, IA) and harvested from 2002 through 2018. Steers and heifers were harvested at liveweights of 1,235.0 +/- 119.8 lb and 1,124.2 +/- 106.7 lb, respectively. Carcass trait trends evaluated for steers and heifers included calculated yield grade score, backfat thickness, hot carcass weight, kidney, pelvic, heart, fat percentage, marbling score, and ribeye area. Results:Calculated yield grade scores increased from 2002 through 2018 for steers and heifers. Fat thickness increased 0.08 in for steers and 0.07 in for heifers, both peaking in 2017 at 0.55 and 0.59 in, respectively. Hot carcass weights ranged from 727 to 780 lb for steers and increased over the 17-year period. Hot carcass weights for heifers ranged from 671 to 711 lb and increased slightly from 2002 through 2018. Kidney, pelvic, heart, fat percentage did not change for steers and heifers. Marbling score increased from 422 to 456 for steers and 449 to 493 for heifers. Ribeye area increased slightly for steers while decreasing slightly for heifers over the 17-year period. The Bottom Line:Corresponding with increases in fat thickness and minimal to no improvement in ribeye area, yield grade scores increased over the past 17 years. Genetic selection pressure on marbling within the beef industry is evident from these data.
Keywords: beef carcass traits; feedlot; marbling